Mucosal immune parameters, immune and antioxidant defence related genes expression and growth performance of zebrafish (Danio rerio) fed on Gracilaria gracilis powder. Issue 83 (December 2018) - Hoseinifar, Seyed Hossein; Yousefi, Samira; Capillo, Gioele; Paknejad, Hamed; Khalili, Mohsen; Tabarraei, Alijan; Van Doan, Hien; Spanò, Nunziacarla; Faggio, Caterina
Abstract: In the present study zebrafish ( Danio rerio ) has been used as model organism to establish the effects of dietary supplementation of Gracilaria gracilis powder (GP) on mucosal and innate immune parameters, antioxidant enzymes, and growth. In order to establish these features, zebrafish were fed for eight weeks with experimental diets containing different levels of Red algae, 0.25, 0.5 and 1% of GP; also, a group was fed with control diet. At the end of the experimental period the antioxidant superoxide dismutase and catalase (SOD, CAT) genes expression, interleukin 1 beta (il-1β),  lysozyme (LYZ), tumor necrosis factor alpha (TNF-α) for immune-related genes expression, total immunoglobulin (Ig), total protein,  alkaline phosphatase (ALP) activity for innate immune parameters, and growth performance have been established. The GP dietary supplementation showed differences in SOD and CAT expression in zebrafish whole body respect to the control group. Non-signifcant differences were noticed among the different groups in case of TNF-α, LYZ and il-1expression ( P  > 0.05). The skin mucus total Ig and total protein in the group fed on 1% of GP were significantly higher respect to control group ( P  < 0.05). 0.25 and 0.5% of GP dietary supplementation significantly enhanced skin mucus ALP activity levels ( P  < 0.05). No significant differences were recorded for growth performances among groups ( P  > 0.05). The results obtained in the present study revealed that G. gracilis could be takes in account as fishes diet supplementation for its immune system stimulants effects. Highlights: Gracilaria gracilis, as supplement in fish diet, influences mucosal immune parameters in Danio rerio. Gracilaria gracilis, as supplement in fish diet, affects on growth in Danio rerio . Gracilaria gracilis, as supplement in fish diet, affects on antioxidant enzymes in Danio rerio .